Epidemiology of Cardiopulmonary Arrest and Outcome of Resuscitation in PICU Across China: A Prospective Multicenter Cohort Study - Xin Ding; Gang Liu; Suyun Qian; Jiansheng Zeng; Ying Wang; Jianping Chu; Qing Chen; Jianli Chen; Yuanyuan Duan; Danqun Jin; Jiaotian Huang; Xiulan Lu; et al. (Frontiers Media S.A., 2022)
ObjectiveTo investigate the epidemiology and the effectiveness of resuscitation from cardiopulmonary arrest (CPA) among critically ill children and adolescents during pediatric intensive care unit (PICU) stay across China.MethodsA prospective multicenter study was conducted in 11 PICUs in tertiary hospitals. Consecutively hospitalized critically ill children, from 29-day old to 18-year old, who had suffered from CPA and required cardiopulmonary resuscitation (CPR) in the PICU were enrolled (December 2017-October 2018). Data were collected and analyzed using the "in-hospital Utstein style." Neurological outcome was assessed with the Pediatric Cerebral Performance Category (PCPC) scale among children who had survived. Factors associated with the return of spontaneous circulation (ROSC) and survival at discharge were evaluated using multivariate logistic regression.ResultsAmong 11,599 admissions to PICU, 372 children (3.2%) had CPA during their stay; 281 (75.5%) received CPR, and 91 (24.5%) did not (due to an order of "Do Not Resuscitate" requested by their guardians). Cardiopulmonary disease was the most common reason for CPA (28.1% respiratory and 19.6% circulatory). The most frequent initial dysrhythmia was bradycardia (79%). In total, 170 (60.3%) of the total children had an ROSC, 91 had (37.4%) survived till hospital discharge, 28 (11.5%) had survived 6 months, and 19 (7.8%) had survived for 1 year after discharge. Among the 91 children who were viable at discharge, 47.2% (43/91) received a good PCPC score (1-3). The regression analysis results revealed that the duration of CPR and the dose of epinephrine were significantly associated with ROSC, while the duration of CPR, number of CPR attempts, ventricular tachycardia/ventricular fibrillation (VT/VF), and the dose of epinephrine were significantly associated with survival at discharge.ConclusionThe prevalence of CPA in critically ill children and adolescents is relatively high in China. The duration of CPR and the dose of epinephrine are associated with ROSC. The long-term prognosis of children who had survived after CPR needs further improvement.